2020
DOI: 10.1177/0731684420943304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physicochemical and mechanical properties with the in vitro degradation of PCL/nHA/MWCNT composite scaffolds

Abstract: The fabrication of biodegradable magnetic poly(caprolactone)(PCL)/nanohydroxyapatite (nHA)/multiwalled carbon nanotube (MWCNT) composite scaffolds by thermally induced phase separation (TIPS) for bone regeneration is reported in this study. The magnetism tests completed on the porous matrices pointed to their ferromagnetic behavior. Both in-vitro degradation and mechanical properties are studied over eight weeks in a phosphate buffered solution (PBS) at 37°C. The addition of MWCNTs at quantities of up to 5% mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Polyester-based scaffolds reinforced with multiwalled carbon nanotubes (MWCNTs) have recently been produced by TIPS [ 19 , 243 , 244 ]. Possessing a wide variety of properties such as electrical, thermal, mechanical and structural, MWCNTs have been reported as proper candidates for biomedical applications [ 245 ].…”
Section: Materials Used In Fabrication Of Tissue Engineering Scaffmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyester-based scaffolds reinforced with multiwalled carbon nanotubes (MWCNTs) have recently been produced by TIPS [ 19 , 243 , 244 ]. Possessing a wide variety of properties such as electrical, thermal, mechanical and structural, MWCNTs have been reported as proper candidates for biomedical applications [ 245 ].…”
Section: Materials Used In Fabrication Of Tissue Engineering Scaffmentioning
confidence: 99%
“…The effect of higher levels of MWCNTs (i.e., 1–10 wt%) and the incorporation of HA (i.e., 10 wt%) on PCL-based scaffold properties was subsequently evaluated. Samples were obtained by ultrasonic dispersion of MWCNTs and nHA particles in PCL-dioxane solutions followed by TIPS to get porous composite matrices [ 243 ]. Despite the excellent properties of CNTs, having other features like high surface area, small diameter and high aspect ratio (>1000) predispose them to form agglomerates when being incorporated as reinforcements into biopolymers, especially in high loading levels [ 248 ].…”
Section: Materials Used In Fabrication Of Tissue Engineering Scaffmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, diverse solution-based techniques have been combined to obtain a 3D porous structure with interconnected pores for TE applications. The TIPS technique is a commonly used method to fabricate TE scaffolds due to its simplicity and effectiveness in adjusting the structure and properties to the application of materials [70,74]. Carfì et al [101] combined TIPS and DIPS to produce a multifunctional scaffold with easy-tunable pore size, porosity, and thickness.…”
Section: Combination Of Solution-based Techniquesmentioning
confidence: 99%
“…It was observed that chondrogenic differentiation and control of vascularization were strongly dependent on the manufacturing process, which, in its turn, is effective in modulating scaffold pore dimensions. Diaz et al [ 74 ] also studied the influence of the use of particles and fabrication parameters of the TIPS process on the thermal and mechanical properties of poly(caprolactone; PCL)/nanohydroxyapatite (nHA)/multiwalled carbon nanotube (MWCNT) composite scaffolds. They found that it is possible to fabricate composite scaffold structures using nano carbons and hydroxyapatite via TIPS by a process optimization based on the application of ultrasonic dispersion.…”
Section: Phase Separationmentioning
confidence: 99%